Military Engagement : Influencing Armed Forces Worldwide to Support Democratic Transitions - Blair, Dennis C. (Book collections on Project MUSE., 2013)
The response of an autocratic nation's armed forces is crucial to the outcome of democratization movements throughout the world. But what exact internal conditions have led to real-world democratic transitions, and have external forces helped or hurt? Here, experts with military and policy backgrounds, some of whom have played a role in democratic transitions, present instructive case studies of democratic movements. Focusing on the specific domestic context and the many influences that have contributed to successful transitions, the authors write about democratic civil-military relations in fourteen countries and five world regions. The cases include Argentina, Chile, El Salvador, Egypt, Hungary, Indonesia, Lebanon, Nigeria, Philippines, Senegal, South Africa, Spain, Syria, and Thailand, augmented by regional overviews of Asia, Europe, Latin America, North Africa and the Middle East, and sub-Saharan Africa.